Assessment of sustainable energy system configuration for a small Canary island in 2030. (1st June 2018) - Meschede, Henning; Child, Michael; Breyer, Christian
Highlights: 100% renewable energy system scenarios were simulated for the island of La Gomera. Scenarios are analysed from the distribution system operator's point of view. A highly electrified transport sector supports the economic transition. A combination of different transition concepts leads to lowest annualised costs. Abstract: Renewable energy systems can play a key role in sustainable energy supply. Because of the fluctuating electricity generation, storage technologies are needed to close the gap between demand and supply. Besides the electricity sector, the transport sector causes high energy demand. In this context, because of their remoteness, islands can be seen as blueprints for possible energy transition pathways. The objective of this paper is to analyse different principle concepts that come into question for a 100% renewable subtropical island from the distribution system operator's point of view. This perspective offers the possibility to account all system costs needed to transfer a centralised energy system into a 100% renewable one and to assume the macroeconomic costs of such a transfer. For the case of La Gomera the economic competitiveness of renewable energy, particularly solar PV and wind power, is shown. All evaluated sustainable scenarios lead to lower annual cost and primary energy demands than the business-of-usual (BAU) scenario based on the cost assumptions used in this study. The analysis underlines that the combination of different technologies will lead to the lowest primary energy demand and to the lowest annualised cost of 10.89 M€ for the entire island energy system, which is 37.2% lower than a BAU scenario.